The Effect of an EHR Order Set on Cancer Screening Order Rates in Community-Based Health Centers - Gold, Rachel; Owens-Jasey, Constance; O'Malley, Jean; Gunn, Rose; Lee, April; Jones, Matthew; Latkovic-Taber, Michaella; Barker, Gordon; Huguet, Nathalie (Applied Clinical Informatics, 2025)
Adoption of electronic health record (EHR)-based clinical decision support tools in community-based health centers might increase the provision of indicated cancer screening orders. We examined: (1) if the use of the care gaps smartset (CGS), an EHR tool that expedites ordering care, is associated with colorectal/cervical cancer (CRC/CVC) screening order rates; and (2) how selected implementation strategies, barriers, and facilitators impact CGS use.Within a sequential mixed methods design, we used multivariate regression to assess associations between clinic- and provider-level CGS use and cancer screening order rates. Tool use rates (3/2018–12/2023) were measured as the rate of encounters at which any orders were placed via the CGS and then categorized by use level. Surveys (n = 81) and semi-structured interviews (n = 11) with clinic staff assessed strategies to improve tool use.Clinics and providers that ever used the CGS had higher CRC screening order rates than non-users. Higher CGS use was associated with better CRC screening order rates. By 12/2023, CRC screening orders were 4.4% (p < 0.05) higher in high-use clinics versus those with no CGS use. CGS use was not associated with CVC screening order rates. Qualitative findings indicate effective CGS use was enhanced by leadership support, clear workflows, and clinic-led training. Barriers to CGS use included low user awareness of/trust in the tool, and tool functions that were not optimized.CGS use can support cancer screening ordering; its adoption may be enhanced by varied training approaches and workflow design.
Keywords: cancer prevention; electronic health record; mixed methods